2018
DOI: 10.3390/nu10121825
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Dietary n-6 Fatty Acid Intake and Hypertension: Effect of Glycated Hemoglobin Levels

Abstract: The relationship between dietary n-6 fatty acids and hypertension is not clear. The metabolic products of n-6 fatty acids include those that control blood pressure, such as prostaglandin and thromboxane, and that differ depending on the extent of glucose tolerance. This cross-sectional study investigated the association of dietary n-6 fatty acid intake on hypertension, and the effects of glycated hemoglobin (HbA1c) value in 633 Japanese subjects aged 40 years and older. Dietary intake was measured using a vali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 32 publications
2
21
0
Order By: Relevance
“…The results of our study were consistent with some previous studies [17,35,36,37]. Levinson et al [35] found n3 fatty acid intake could reduce the risk of hypertension, and the study conducted by Knapp et al [36] also found this negative association.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The results of our study were consistent with some previous studies [17,35,36,37]. Levinson et al [35] found n3 fatty acid intake could reduce the risk of hypertension, and the study conducted by Knapp et al [36] also found this negative association.…”
Section: Discussionsupporting
confidence: 93%
“…Levinson et al [35] found n3 fatty acid intake could reduce the risk of hypertension, and the study conducted by Knapp et al [36] also found this negative association. Meanwhile, our study also indicated n6 fatty acid intake could reduce the risk of hypertension, and the study conducted by Nakamura et al [17] also indicated this negative association. The association between n6:n3 ratio and the risk of hypertension was not significant in our study, and Mirmiran et al [37] also found this not significant association.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…These baseline data were derived from the SHIKA study, which is a longitudinal population-based observational study conducted to describe the health status of the population in a town model and investigate approaches to prevent life-related diseases, such as hypertension, diabetes, allergic diseases and liver diseases. This study population has been reported previously [17]. In brief, there were 22,314 residents in Shika town in March 2014, 18,839 of whom were middle-aged (40 years or older) [18].…”
Section: Methodsmentioning
confidence: 99%
“…It includes interviews, questionnaires, and health examinations. Health examination data was collected between March 2014 and January 2018 from the residents of Shika, a town with more than 20,000 residents ( 20 ), located in a north area of Ishikawa Prefecture, Japan ( 21 ). The present study was conducted from December 2017 through January 2018 with four model districts in Shika being selected, including Horimatsu, Higashi-Masuho, Tsuchida, and Togi.…”
Section: Methodsmentioning
confidence: 99%